REVIEW OF THE ARTICLE “WORK AND ALIENATION IN THE PHILOSOPHY OF KARL MARX” - Araújo, Daniel Silva de; Macedo, Aurilene Alves de; Sousa, Alexandre de Araújo; Alves, Alexandra Leandro Correia (Revista Coleta Científica, 2021)
This is a review of the article entitled, Work and Alienation in Philosophy by Karl Marx. This article is by: Soraia Coelho Pacheco. Graduated in LETTERS, by UNIDERP/ANHANGUERA. Graduated in Degree in Philosophy by the Higher Education Center of Caxias-CESC/UEMA.